Soil Health Profile in Claypan Soils - C. J. Hsiao; G. F. Sassenrath; C. Rice; G. Hettiarachchi; L. Zeglin (Kansas Agricultural Experiment Station Research Reports, 2018)
Healthy soil is the foundation of a sustainable agronomic production system. Microorganisms include bacteria (such as actinomycetes), fungi, and protozoa. Soil microorganisms, or microbes, exist in large numbers in soils and are critical for decomposition of organic residues and nutrient recycling. Soils with ample and diverse microbial populations can provide more essential nutrients for crop growth and development. Soil microbial properties are considered one of the major indicators of soil health. Soil microbial properties can be measured by the activity and the composition of micro-organism populations. Phospholipid fatty acids (PLFA) are the primary components of cell membranes, they can be used to estimate the total amount, or biomass, of bacterial and fungal microbes in the soil. The assay measures the amount of phospholipid fatty acids per weight of soil (nmol PLFA/g soil) and is expressed as the PLFA microbial biomass. Microorganisms within the soil release enzymes that degrade organic material to release nutrients needed to support the microbial community. These nutrients are also used to support plant growth. One of the major groups of soil enzymes, hydrolases, decomposes soil material to release carbon, nitrogen, and phosphorus. By measuring the enzymatic activity of these hydrolases within the soil profile, calculated as the amount of substrate decomposed over time for a given weight of soil (nmol/hr/g soil), we can determine the activity of the microbial community. Claypan soils have a dense, impermeable subsoil that impedes root system development. The soils can be productive, but the productive capacity is often limited by shallow topsoil depth. The poorly drained clayey layer saturates the surface soils, impairs root growth, and exacerbates soil erosion compared to well-drained soils. Crop production on claypan soils requires careful management to maintain productive capacity. It is important to understanding the role of soil microbial properties integrated with soil physical and chemical properties to provide optimal management practices in claypan soils. Little is known about soil microbial properties in claypan soils or how the textural changes in claypan soils impact microbial activity and communities. In this report, we present how management practices influenced soil microbial properties and describe how soil texture mediates changes in soil microbial properties with depth in claypan soil.
Keywords: Soil health; soil microbial property; phospholipid fatty acid analysis; extracellular enzyme activity analysis